Indigenous, Moorish and African Women: Mestizajes and Representation of a Loving Coexistence in Chile [Las Mujeres Indígenas, Moriscas y Africanas: Los Mestizajes y la Representación de la Sociabilidad Amorosa en Chile] - Salinas-Campos, M (2012)
Mestizaje has been understood and taught from a colonial and patriarchal perspective as the existence or the abandonment of a European father . Thus, the mestizo a historical negativity, or a permanent reminder of the violence of father . Whereas its reality and imagination are far richer and more complex. In the process of cultural mixing, the active and leading role of non-western women gave the ethnic dynamic process more vitality and creativity than that presented by official images from the colonial West. Indigenous, Moorish, and African women established a way of life where the sentiment of love became fundamental part of human coexistence.